PRODUKSI SERASAH (GUGURAN DAUN) PADA BERBAGAI JENIS MANGROVE DI BANGKALAN - Wahyu Andy Nugraha (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2010)
This research was conducted on July to September 2009. Mangrove litterfall were trapped with 30 litter traps which were plotted under mangrove canopy 1.5 m above the ground, hence the traps were avoided from tide. In this research, we use Rhizopora mucronata, Rhizopora apiculata and Bruguera sp. 10 litter traps were used on each species. Litter traps were made from polyetilen with size of 1x1x0,5 m3. Mangrove litterfall were collected every two weeks for 3 months. The production rate of mangrove litterfall in Bangkalan were 4.08-18.38 g/tree/day. The fastest production rate of mangrove litterfall was found on Rhizopora mucronata with 64.56%, followed by Rhizopora apiculata and Brugueira sp with 24.32% and 11.12%, respectively. Key Words : mangrove litterfall, Bangkalan, Rhizopora